Balance and optimization model of interconnected energy carrier transmitting and distributing systems in the context of general energy balance - Novoseltsev A.V.; Kaplin M.I. (General Energy Institute of the National Academy of Sciences of Ukraine, 2009)
Application of balance and optimization models of production type to the analysis of the energy balances of fuel-energy sector of economy is considered. Interconnected networked subsystems of energy carrier transmission and distribution and their modeling principles are discussed in the aspect of the balance and optimization models adaptability.